Self-Efficacy in The Novel “A Street Cat Named Bob” By James Bowen (2012) - Gifari, Muhammad Al; Anwar, Desvalini (English Language and Literature, 2024)
This research is an analysis of  the novel "A Street Cat Named Bob" by James Bowen (2012). The researcher aims to describe how to develop self-efficacy with the help of social support in achieving goals. The Researcher employs Sigmund Freud's Psychoanalytic theory to explain how the 3 basic human traits namely Id, Ego, and Superego that influence a person in their pursuit of success. This thesis posits that one effective way to achieve goals is by enhancing self-efficacy, which can be supported by social networks. The research explores the elements of the novel, such as tone, setting, characters, point of views, to interpret and argue about the novel. In conclusion, the research reveals that a key factor influencing the character's success is the development of self-efficacy, there are four key factors: experiences encountered, self-belief, stress reducers, and finally, social persuasion. In the end, the researcher successfully identified self-efficacy, closely related to his environment, including Bob, the street cat which has provided social support.